Why do shoppers use cash? Evidence from shopping diary data - Naoki Wakamori; Angelika Welte (Bank of Canada, 2012)
Recent studies find that cash remains a dominant payment choice for small-value transactions despite the prevalence of alternative means of payment such as debit and credit cards. For policy makers an important question is whether consumers truly prefer using cash or merchants restrict card usage. Using the Bank of Canada's 2009 Method of Payment Survey, we estimate a generalized multinomial logit model of payment choices to extract individual heterogeneity (demand-side factors) while controlling for merchants' acceptance of cards (supply-side factors). Based on a counterfactual exercise where we assume universal card acceptance among merchants, we find that some consumers would decrease their cash usage but the magnitude of this decrease is small. Our results imply that the use of cash in small-value transactions is driven mainly by consumers' preferences.
Keywords: G2; D1; C2; 330; Bank notes; Econometric and statistical methods; Financial services